Evaluation of phyllite and basalt associated with Azospirillum brasilense inoculation in oat cultivation - Galina, Jardel; Oliveira, Patrícia Aparecida de; Rosalen, Karina; Busnello, Fábio José; Baretta, Carolina Riviera Duarte Maluche (Ciência agronômica, 2025)
ABSTRACT The objective of this study was to evaluate the performance of white oat in the presence of phyllite and basalt dusts associated with Azospirillum brasilense inoculation. The experiment was conducted in a completely randomized design (n = 5) with the following treatments: FB, fertilizer + basalt dust; FP, fertilizer + phyllite dust; FA, fertilizer + Azospirillum brasilense; FBA, fertilizer + basalt dust + Azospirillum brasilense; FPA, fertilizer phyllite dust + Azospirillum brasilense; C, Control. The following variables were evaluated: plant variables - emergence speed index (ESI), Fresh matter (FM), dry mass (DM), root length (RL), plant height (H) and root dry mass (RDM); and soil variables - phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), aluminum (Al), potential soil acidity (PSA), base saturation (BS) and cation exchange capacity (CEC). Phyllite application resulted in lower RL, but promoted the highest H and FM. On the other hand, basalt application increased RDM production when associated with inoculation. In addition, there was an increase in the base content of the soil when phyllite dust and basalt dust were applied. It can be observed that, throughout the cuts, the association of rock dusts with inoculation allows more stability of FM and DM production, increasing the forage potential of oat in the third cut by up to 20%. It is concluded that the association of phyllite and basalt with Azospirillum brasilense affects the chemical properties of the soil, promoting benefits to white oat cultivation.